Establishing Benchmark Percentiles for the Classification of Body Fat Percentage of Professional Male Athletes Competing in Combat Sports through Bioimpedanciometry - Marius Baranauskas; Ingrida Kupčiūnaitė; Rimantas Stukas (Applied Sciences, 2023)
Body composition as a meaningful factor can result in physiological responses in both the physical body and general health status. Nevertheless, the schemes for establishing cut-off points for identifying the classifications of the body fat percentage of athletes competing in combat sports still include gaps. The aim of this study was, by using bioimpedanciometry, to calculate the percentiles for the classification of body fat percentages in Lithuanian professional male athletes (n = 52) competing in combat sports with weight classes. A total of 52 Lithuanian professional male athletes competing in combat sports with weight classes were evaluated using a multi-frequency bioelectrical impedance analysis method with frequencies ranging from 1 kHz to 1000 kHz. Percentiles P3, P10, P25, P50, P75, P90, and P97 were used to determine the classification. As a consequence, the following classification categories were assigned: 6.6–7.8% (extremely low); 7.9–10.9% (very low); 11.0–14.7% (below normal); 14.8–18.8% (normal); 18.9–21.5% (above normal); 21.6–29.3% (very excessive); and ≥29.4% (extremely excessive). The assessment of body composition in combat sports athletes identified an inverse association between higher body fat levels and a decrease in the muscle-to-fat ratio (β –1.3, 95% confidence interval (CI): –1.5; –1.0, p < 0.001). The relationship between lower body fat percentage and lighter weight categories in which combat sports athletes from different combat sports were competing has been identified (β 0.3%, 95% CI: 0.2; 0.3, p < 0.0001). The established cut-off points may assist sports medicine professionals and sports dietitians in monitoring the adiposity of combat sports athletes.